2015
DOI: 10.1016/j.virol.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of the c-MYC oncoprotein is required for cooperation with the HTLV-1 p30 II accessory protein and the induction of oncogenic cellular transformation by p30 II /c-MYC

Abstract: The human T-cell leukemia retrovirus type-1 (HTLV-1) p30II protein is a multifunctional latency-maintenance factor that negatively regulates viral gene expression and deregulates host signaling pathways involved in aberrant T-cell growth and proliferation. We have previously demonstrated that p30II interacts with the c-MYC oncoprotein and enhances c-MYC-dependent transcriptional and oncogenic functions. However, the molecular and biochemical events that mediate the cooperation between p30II and c-MYC remain to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 99 publications
0
36
0
Order By: Relevance
“…HTLV-1 p30 II distinctly enhances c-Myc transforming activity, engendering S-phase progression and polyploidy through the interaction with the Myc-associated transcriptional coactivators TRRAP/p434 and the histone acetyltransferase TIP60 and the stabilization of HTLV-1 p30 II /Myc-TIP60 chromatin-remodeling complexes ( 73 ). Indeed, the retroviral p30 II accessory protein is recruited on the E-box enhancer elements within the endogenous cyclin D2 promoter along with c-Myc and the acetyltransferases TIP60 and p300, where lysine-acetylation of the c-Myc oncoprotein contributes to HTLV-1-induced carcinogenesis ( 79 ). Hence, in the context of HTLV-1 infection, Tax expression, in addition to p30 II , appear to play a crucial role in polyploidy induction.…”
Section: Introductionmentioning
confidence: 99%
“…HTLV-1 p30 II distinctly enhances c-Myc transforming activity, engendering S-phase progression and polyploidy through the interaction with the Myc-associated transcriptional coactivators TRRAP/p434 and the histone acetyltransferase TIP60 and the stabilization of HTLV-1 p30 II /Myc-TIP60 chromatin-remodeling complexes ( 73 ). Indeed, the retroviral p30 II accessory protein is recruited on the E-box enhancer elements within the endogenous cyclin D2 promoter along with c-Myc and the acetyltransferases TIP60 and p300, where lysine-acetylation of the c-Myc oncoprotein contributes to HTLV-1-induced carcinogenesis ( 79 ). Hence, in the context of HTLV-1 infection, Tax expression, in addition to p30 II , appear to play a crucial role in polyploidy induction.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, in contrast to other cancers, the p53 tumor suppressor is rarely mutated in HTLV-1-transformed ATLL clinical isolates (Zane et al, 2012; b Pise-Masison et al, 1998; Tabakin-Fix et al, 2006; Mengle-Gaw and Rabbitts, 1987) -suggesting that p53-regulated target genes may contribute to viral pathogenesis. The HTLV-1 latency-maintenance factor p30 II interacts with the MYSTfamily acetyltransferase TIP60 and inhibits lysine K120-acetylation of p53 (Awasthi et al, 2005;Romeo et al, 2015Romeo et al, , 2018 which differentially regulates the expression of p53-dependent pro-apoptotic genes (Sykes et al, 2006;Tang et al, 2006;Kurash et al, 2008;Dar et al, 2013;Xu et al, 2014). We recently demonstrated that p30 II activates p53 and induces the expression of p53-regulated pro-survival signals, including the TIGAR, which is required for its cooperation with cellular (e.g., c-Myc) and viral (Tax and HBZ) oncoproteins (Hutchison et al, 2018;Romeo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated in Hutchison et al (2018) that the HTLV-1 latency-maintenance factor p30 II (Nicot et al, 2004;Younis et al, 2004;Zhang et al, 2000;Bartoe et al, 2000) inhibits Tax-induced cytotoxicity and cooperates with the viral transactivator to promote oncogenic colony formation in vitro, dependent upon the activation of p53-regulated pro-survival signals, including the TP53-induced glycolysis and apoptosis regulator (TIGAR; Bensaad et al, 2006;Bensaad et al, 2009) which suppresses Tax-induced oxidative stress. p30 II interacts with the MYST-family acetyltransferase TIP60 (Awasthi et al, 2005;Romeo et al, 2015) and inhibits lysine K120acetylation of the p53 protein (Romeo et al, 2018) which differentially regulates the expression of p53-dependent pro-apoptotic genes (Sykes et al, 2006;Tang et al, 2006;Kurash et al, 2008;Dar et al, 2013;Xu et al, 2014). Interestingly, the p53 tumor suppressor is mutated in nearly half of all cancers; however, it is rarely mutated in HTLV-1+ ATLL clinical isolates which frequently contain high levels of wildtype p53 (Zane et al, 2012;b Pise-Masison et al, 1998;Tabakin-Fix et al, 2006;Mengle-Gaw and Rabbitts, 1987), suggesting the subversion of p53-regulated target genes may contribute to viral carcinogenesis (Hutchison et al, 2018;Romeo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The p12 protein, or its proteolytic product p8, promotes T cell activation, virus transmission, and escape from CTL and NK cell killing [4,7]. The p30 protein is a latency maintenance factor that cooperates with c-Myc in oncogenesis [8]. Unlike other retroviruses, HTLV-1 also encodes an anti-sense transcript that produces the HBZ, helix-basic loop zipper protein [9].…”
Section: Introductionmentioning
confidence: 99%